Conceptualizing financial risk and investment diversification towards the efficiency of waqf institutions in Malaysia - Rubayah Yakob,; Mohd Hafizuddin Syah Bangaan Abdullah,; Nurul Hidayah Md Razali,; Hairolanuar Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to conceptualize on how financial risks i.e., liquidity and credit risk, and investment diversification relate to waqf institution’s efficiency in Malaysia. Past studies were reviewed to identify the relevant theories and empirical evidence relating to efficiency, liquidity risk, credit risk and investment diversification. Conceptually, it is found that the inefficiency of waqf institutions in managing its waqf property is mainly due to the exposure of liquidity and credit risk. However, investment diversification strategies allow waqf institutions to generate higher potential returns and subsequently enhance its financial resources. Thus, diverse investment portfolio could moderate the impact of liquidity and credit risk on the efficiency of waqf institutions. In fact, waqf institution’s efficiency has been rarely examined in studies due to its unique operation and the absence of accurate measurement. This research proposes a framework that is the first to link the efficiency of the waqf institution with financial risk, and investment diversification as a moderator. This could be an impetus for future empirical research. Indeed, the framework has indirectly emphasized the importance of risk management for waqf institutions.